Differential Effects Of Maternal Sensitivity To Infant Distress And Non-Distress On Social-Emotional Functioning - Leerkes, Esther M. (2009)
Associations between maternal sensitivity to infant distress and non-distress and infant social-emotional adjustment were examined in a subset of dyads from the NICHD Study of Early Child Care (N = 376). Mothers reported on infant temperament at 1 and 6 months postpartum, and maternal sensitivity to distress and non-distress were observed at 6 months. Child behavior problems, social competence, and affect dysregulation were measured at 24 and 36 months. Maternal sensitivity to distress but not to non-distress was related to fewer behavioral problems and higher social competence. In addition, for temperamentally reactive infants, maternal sensitivity to distress was associated with less affect dysregulation. Sensitivity to non-distress only prevented affect dysregulation if sensitivity to distress was also high.